2019
DOI: 10.4102/sajp.v75i1.1319
|View full text |Cite
|
Sign up to set email alerts
|

Post-tuberculosis health-related quality of life, lung function and exercise capacity in a cured pulmonary tuberculosis population in the Breede Valley District, South Africa

Abstract: Background Pulmonary tuberculosis (PTB) remains a major concern worldwide. Albeit curable, PTB continues to negatively affect patients’ health-related quality of life (HRQoL) and functioning even after cure. Objectives To describe the demographics, respiratory symptoms, pulmonary airflow patterns, HRQoL and exercise capacity of cured PTB patients, in the Breede Valley district of South Africa. Methods A cross-sectional study conducted at five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
(38 reference statements)
4
21
0
6
Order By: Relevance
“…A study by Pasipanodya et al [25] reported a 13-point increase (worsening QoL) in total SGRQ score after TB treatment. This was corroborated by a study by Daniels et al [27] who used a different HRQoL assessment tool, the Short Form 12 (SF-12) health survey questionnaire, and reported poor HRQoL post-TB in a South African population. Similar to our findings, these studies also report lower HRQoL in relation to the physical domain compared with the mental domain that was independent of gender.…”
Section: Discussionsupporting
confidence: 58%
“…A study by Pasipanodya et al [25] reported a 13-point increase (worsening QoL) in total SGRQ score after TB treatment. This was corroborated by a study by Daniels et al [27] who used a different HRQoL assessment tool, the Short Form 12 (SF-12) health survey questionnaire, and reported poor HRQoL post-TB in a South African population. Similar to our findings, these studies also report lower HRQoL in relation to the physical domain compared with the mental domain that was independent of gender.…”
Section: Discussionsupporting
confidence: 58%
“… 16 A similar study in rural South Africa found comparatively more preserved lung function and fewer symptoms but much reduced 6MWD (mean: 294 m) compared to our population. 17 A Malawian cohort demonstrated lower symptom burden than our population, with 12% having symptom-related impairment in their ability to work 1 year after treatment completion, with a mean 6MWD of 611 m. 7 Whether there is an effect of urbanisation on PTLD needs to be established.…”
Section: Discussionmentioning
confidence: 88%
“…Affected patients can have restrictive, obstructive, or mixed patterns on spirometric testing ( 34 ) and this can manifest as various chronic lung diseases including pulmonary fibrosis, emphysema, and bronchiectasis ( 35 ). Consequently, TB survivors have shortened life expectancies, with one model predicting an average loss of 3.6 years of life ( 36 ), and this is associated with a reduced perceived mental health-related quality of life (HRQoL) even after microbiological cure ( 37 ). The extent of radiological disease severity at diagnosis is the most important determinant of residual pulmonary function post treatment ( 33 , 38 , 39 ), however the mechanisms that link initial bacterial infection to the development of fibrosis are poorly understood.…”
Section: Immunopathology In Tb: the Matrix Degrading Phenotypementioning
confidence: 99%